Ten years of the Helsinki Declaration on patient safety in anaesthesiology: An expert opinion on peri-operative safety aspects - Preckel, Benedikt; Staender, Sven; Arnal, Daniel; Brattebø, Guttorm; Feldman, Jeffrey M.; Ffrench-O'Carroll, Robert; Fuchs-Buder, Thomas; Goldhaber-Fiebert, Sara N.; Haller, Guy; Haugen, Arvid S.; Hendrickx, Jan F. A.; Kalkman, Cor J.; et al. (European journal of anaesthesiology, 2020)
Patient safety is an activity to mitigate preventable patient harm that may occur during the delivery of medical care. The European Board of Anaesthesiology (EBA)/European Union of Medical Specialists had previously published safety recommendations on minimal monitoring and postanaesthesia care, but with the growing public and professional interest it was decided to produce a much more encompassing document. The EBA and the European Society of Anaesthesiology (ESA) published a consensus on what needs to be done/achieved for improvement of peri-operative patient safety. During the Euroanaesthesia meeting in Helsinki/Finland in 2010, this vision was presented to anaesthesiologists, patients, industry and others involved in health care as the 'Helsinki Declaration on Patient Safety in Anaesthesiology'. In May/June 2020, ESA and EBA are celebrating the 10th anniversary of the Helsinki Declaration on Patient Safety in Anaesthesiology; a good opportunity to look back and forward evaluating what was achieved in the recent 10 years, and what needs to be done in the upcoming years. The Patient Safety and Quality Committee (PSQC) of ESA invited experts in their fields to contribute, and these experts addressed their topic in different ways; there are classical, narrative reviews, more systematic reviews, political statements, personal opinions and also original data presentation. With this publication we hope to further stimulate implementation of the Helsinki Declaration on Patient Safety in Anaesthesiology, as well as initiating relevant research in the future.